BUDIDAYA KIJING TAIWAN (Anodonta woodiana, Lea) DENGAN CARA PEMELIHARAAN BERBEDA - Srie Rahayu, Sata Yoshida; Rachman, Boedi (Fakultas Matematika dan ilmu pengetahuan Alam. Universitas Pakuan.)
Unionidae Shells have a potential economic importance for humans. These shells can be used as commodity farming inland fisheries due to the their flesh can be eaten, have a protein content 7.37 grams in 100 grams of meat, the shell is useful for industrial raw material studs and animal feed, as well as this animals can be cultivated as a pearling. The purpose of this research is to know a good way where maintenance against the growth of Anodonta woodiana Pearly shells, Lea. materials in this research is the parent of mussels reared in freshwater pool with two different ways, first is hanged in koja (basket and second way is removed at the bottom of the pool. Monitoring the quality of the physics and chemistry of water is done every week i.e. parameters: temperature, pH, DO, NH3, calcium, debit and brightness. Identification of plankton swimming is done every week. Clam growth measured on a weekly basis: average weights, Ø length of the shell, the shell width, Ø and Ø thicker shell and survival. Average weight of shells and shell growth being maintained well with the observed two different ways during the 6 week look is always incremented even though relatively slow. Maintenance of basic dribbling off better against the survival and growth of diameter shells compared to how hung in various spices. Key words : Anodonta woodiana, Lea, was hanged in the basket, off base.